Implantación de la contabilidad en “agropecuario el finquero”, del canton Loja, parroquia Malacatos, período enero -marzo del 2015 - Puglla Pineda, Wendi Beatriz (2016)
This research paper entitled "IMPLEMENTATION OF ACCOUNTING IN" AGRICULTURE the farmer ", of Canton Loja, PARISH Malacatos period January-March 2015", was developed in order to provide the company with an accounting system to meet your needs allowing proper processing of the financial information generated by the company, it lacked basic information related to the valuation of assets and liabilities and as a consequence the assets of the business were unknown. The research was made in compliance with one of the pre-qualification as Engineer in Accounting and Auditing, CPA requirements. Were complied with the objectives starting from the compilation of the source documents, the Chart of Accounts was designed,thenthe operatingaccountswhichis encodedwas drawn, describes and analyzeseach of theaccounts, theuprisingtook placeinitial inventory, its initialsituation, and their respectivejournalmajorization, the worksheetand postitat the end ofperiodfinancial statementsthat reflectthesituation of the companyis made Finally, conclusionsand recommendations aremade for consideration bythe ownerfor growth development of your business.